Creep Compliance and Percent Recovery of Oklahoma Certified Binders Using the Multiple Stress Creep Recovery (MSCR) Method - (:unkn) unknown (Oklahoma City, OK : Oklahoma Department of Transportation, 2015., 2015)
A laboratory study was conducted to develop guidelines for the Multiple Stress Creep Recovery (MSCR) test method for local conditions prevailing in Oklahoma. The study consisted of commonly used binders in Oklahoma, namely PG 64-22, PG 70-28, and PG 76-28. The testing program also included binders recovered from four reclaimed asphalt pavement (RAP) samples and Sasobit¬-modified virgin binders. Non-Recoverable Creep Compliance (Jnr) and MSCR %Recovery, obtained from the MSCR test data, were analyzed for the MSCR grading. In addition, the Asphalt Institute (AI) recommended Polymer and Quadrant methods were followed in interpreting the test data. Analyses of test results showed that the AASHTO T 350 and AASHTO T 332 recommended Jnr criteria could be followed in the MSCR-based grading for conditions prevailing in Oklahoma. It was observed that 97% of the tested polymer-modified binders met the Asphalt Institute (AI) recommended minimum %Recovery and stress sensitivity. Acceptable %Recovery limits are proposed for both PG 70-28 and PG 76-28 binders without penalizing a significant number of suppliers or users. It was also found that an addition of 3% Sasobit¬ would reduce the rut depth by half compared to other binders. It is expected that these guidelines will assist ODOT in a successful transition to the latest MSCR specifications for binders.
Keywords: Rutting; MSCR; Elastic Recovery; Compliance; Creep